A Bayesian Approach to Real Options: The Case of Distinguishing between Temporary and Permanent Shocks - GRENADIER, STEVEN R.; MALENKO, ANDREY (Journal of Finance, 2010)
ABSTRACT Traditional real options models demonstrate the importance of the “option to wait” due to uncertainty over future shocks to project cash flows. However, there is often another important source of uncertainty: uncertainty over the permanence of past shocks. Adding Bayesian uncertainty over the permanence of past shocks augments the traditional option to wait with an additional “option to learn.” The implied investment behavior differs significantly from that in standard models. For example, investment may occur at a time of stable or decreasing cash flows, respond sluggishly to cash flow shocks, and depend on the timing of project cash flows.